Chemical profile and biological activities of Cedrelopsis grevei H. Baillon bark essential oil. (2nd January 2018) - Tardugno, R.; Spagnoletti, A.; Grandini, A.; Maresca, I.; Sacchetti, G.; Pellati, F.; Benvenuti, S.
Abstract: Cedrelopsis grevei H. Baillon bark, endemic plant from Madagascar, is used in folk medicine for the treatment of rheumatism, muscular pain, and for its antifungal and antibiotic activities. In this paper, the phytochemical composition, antioxidant, antimicrobial, and cytotoxic activities of C. grevei bark essential oil (EO), its non-polar (I and II) and polar (III) fractions and its main compounds (ishwarane, β-elemene and α-copaene) were investigated. The GC–MS analysis pointed out the presence of 36 components, representing about 80% as semi-quantitative characterization of the total. The presence of ishwarane, β-elemene and α-copaene as the main constituents highlighted its peculiar composition as a sesquiterpene-rich phytocomplex. Moreover, the quantification was performed for the first time by means of the experimental and predicted response factors (ERFs and PRFs, respectively). As regards the biological activity, C. grevei EO and its fractions showed weak antioxidant activity against Trolox. The whole EO demonstrated instead considerable antimicrobial activity against Staphylococcus aureus and Staphylococcus epidermidis, while its polar-fraction evidenced an interesting bioactivity against Pseudomonas aeruginosa and Candida albicans . Finally, C. grevei EO and its fractions exhibited an interesting cytotoxic activity on human lung cancer cells (A549) and human colorectal cancer cells (CaCo-2). Abstract :